Potentiating doxorubicin activity through BCL-2 inhibition in p53 wild-type and mutated triple-negative breast cancer - Schreiber, Anna R.; Smoots, Stephen G.; Jackson, Marilyn M.; Bagby, Stacey M.; Dus, Evan D.; Dominguez, Adrian T. A.; Binns, Cameron A.; Pitts, Todd M.; Diamond, Jennifer R. (Frontiers in Oncology, 2025)
BackgroundTriple-negative breast cancer (TNBC) is an aggressive sub-type of breast cancer that is associated with higher rates of recurrent disease. Chemotherapy with an anthracycline is an integral part of curative therapy but resistance remains a clinical problem. Cellular senescence is a terminal cell fate that has been observed in models of doxorubicin resistance. Identifying novel combinations with doxorubicin to eliminate senescent cells and promote apoptosis may lead to improved clinical outcomes. The purpose of this study was to investigate the combination of doxorubicin with the pro-apoptotic BCL-2 inhibitor venetoclax in TNBC cell lines and to assess the role of p53 in cellular senescence and apoptosis.MethodsTNBC cell lines with wild-type (WT), mutated or knocked-down (KD) p53 were treated with doxorubicin, venetoclax or the combination in vitro and evaluated for impacts on viability, proliferation, apoptosis, and senescence. Down-stream markers of apoptosis were also assessed to evaluate cellular mechanistic changes. An in vivo TNBC MDA-MB-231 murine model was used to assess tumor growth, cellular proliferation, and senescence changes following treatment with doxorubicin, venetoclax or combination.ResultsVenetoclax with doxorubicin had synergistic antiproliferative activity against TNBC cell lines and increased apoptosis. The addition of venetoclax to doxorubicin reduced senescent cells in a p53-independent manner. In vivo, the addition of venetoclax to doxorubicin improved tumor growth inhibition and reduced senescent cells.ConclusionThe combination of doxorubicin with venetoclax is promising for the treatment of p53-WT and mutated TNBC and this work supports further investigation.